2017
DOI: 10.1080/02640414.2017.1318217
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of upper leg EMG frequency content during cycling

Abstract: Reproducibility of frequency content from surface electromyography (sEMG) signals has not been assessed and it is unknown if incremental load testing design could affect sEMG in cycling. The goals of this study were to assess the reproducibility of measures from sEMG frequency content between sessions and to compare these frequency components between a ramp and a step incremental cycling test. Eighteen cyclists performed four incremental load cycling tests to exhaustion. Two tests were performed using a step i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Several studies have examined the repeatability of sEMG bursts within individuals cycling under the same conditions across multiple days. These studies have demonstrated high reproducibility of the magnitude components of the signals (Laplaud et al 2006 ; MacDonald et al 2008 ; Travis et al 2011 ; Bini et al 2017 ), with one finding high reproducibility of the temporal components (Jobson et al 2013 ). These findings suggest that the same muscle activation patterns are consistently used during cycling, indicating good potential for these measures to be used for monitoring changes in clinical and sports training settings.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the repeatability of sEMG bursts within individuals cycling under the same conditions across multiple days. These studies have demonstrated high reproducibility of the magnitude components of the signals (Laplaud et al 2006 ; MacDonald et al 2008 ; Travis et al 2011 ; Bini et al 2017 ), with one finding high reproducibility of the temporal components (Jobson et al 2013 ). These findings suggest that the same muscle activation patterns are consistently used during cycling, indicating good potential for these measures to be used for monitoring changes in clinical and sports training settings.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used biopotential measurement systems such as surface electromyograms (EMG) have demonstrated use in these findings, specifically in identifying the patterns of contractile amplitudes and frequencies during a fatiguing exercise (1)(2)(3)(4)(5)(6). For example, fatiguing muscles show an increase in EMG contractile amplitude that correlates to the number of recruited motor neurons, as well as a low-frequency shift in the raw EMG signal (7)(8)(9)(10). These frequency-based analyses are a popular strategy to measure the presence of fatigue and adaptation in short-term applications such as on a set-to-set basis (2,11,12).…”
Section: Introductionmentioning
confidence: 99%